PENGARUH PENGGUNAAN APLIKASI KEUANGAN PAPARAN MEDIA SOSIAL DAN KEBIASAAN BELANJA TERHADAP PENGELOLAAN KEUANGAN MAHASISWA - Ertines Karmenisa Lubis; Puput Deminar Br Rajagukguk; Sheila Mangunsong; Siti Dini; Dwita Sakuntala (Mount Hope Economic Global Journal, 2026)
This study aims to analyze the influence of financial application usage, social media exposure, and shopping habits on students' financial management. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires from 150 student respondents. The results of the instrument test showed that all statement items were valid and reliable. The clinical assumption test showed that the data were normally distributed and there was no multicollinearity and heteroscedasticity. The results of the regression analysis showed that the use of financial applications had a positive and significant effect on students' financial management. Conversely, social media exposure and spending habits had a significant negative impact on students' financial management. Simultaneous test results showed that all three independent variables significantly influenced students' financial management. The coefficient of determination (CoE) of 0.746 indicates that 74.6% of the variation in students' financial management can be explained by the use of financial applications, social media exposure, and spending habits, while the remaining influence was attributed to other factors outside the study. The research findings indicate that utilizing financial technology helps students manage their finances more effectively, while high social media exposure and spending habits tend to decrease students' financial management skills.